Klasyfikacja europejskiej przestrzeni regionalnej ze względu na identyfikatory gospodarki opartej na wiedzy - Strahl, Danuta; Markowska, Małgorzata (Classification of European Regional Space with Regard to Factors Identifying Knowledge Based Economy, 2007)
The article takes up an attempt to identify European regional space of NUTS 2 level with regard to the level of knowledge based economy (KBE) and putting particular emphasis on national and European centers. Methods of multidimensional statistical analysis constituted the analytical tool. The following variables were accepted as factors identifying knowledge based economy: share of employed tertiary education graduates in the overall number of population aged 25-64, share of population participating in continual education in the overall population number aged 25-64, number of patents per 1 million of workforce, share of population employed in services "based on knowledge", share of high- and mid-tech industry employees.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 261-269